Análise de risco à saúde diante da exposição a poluentes liberados durante o processo de cocção de alimentos - Uemura, Michele Leiko (2013)
Introduction: According to the Household Budget Survey (HBS) from 2008 to 2009, the percentage of expenditure on food outside the home among the population residing in urban areas was 33.1%. The activity held in commercial kitchens is characterized as a process that uses intensively its workforce, for prolonged periods and in inadequate conditions. The assessment of the levels of pollutants in the Buffet restaurants both in the kitchen and in the hall is relevant for surveying the risk to vulnerable individuals. Methods: Cross-sectional study was done, from May to July 2012, which ten commercial Buffet type restaurants were analyzed, evaluating the air pollutant concentrations within the kitchen and salon service in the city of Santos. Five kitchen staff and five ballroom, totaling 100, were selected in 10 restaurants. The European Community Respiratory Health Survey (ECRHS) for adults was used to collect morbidity data. The data collection of particulate matter 2.5 ¿m was performed in duplicate, in the kitchens and lounge during food preparation. NO2 passive samplers were placed inside the kitchen and service room thirteen consecutive days in triplicate. Descriptive analyzes were performed for all variables. Quantitative variables were calculated by measures of central tendency and dispersion. Qualitative variables were described in terms of their absolute and relative numbers. The differences between the averages of the pollutants in the kitchen and salon service were done through the testing u t test, Mann-Whitney test. The differences in the concentrations of pollutants in the kitchen and salon service were done through analysis of variance for independent samples (ANOVA). In situations where there was a difference between the measurements was applied Tukey-HSD test to identify these differences. Results: The levels of PM2, 5 issued during cooking of food were 60-459 g/m3 for kitchens and 5-80 ¿g/m3 in the halls, and NO2 between 60 and 180 ¿g/m3 in kitchens and 40 and 60 ¿g/m3 in the halls, the differences being statistically significant. The prevalence of respiratory symptoms suggestive of asthma in total workers surveyed was 20%. But there was no association between the occurrence of respiratory morbidity and perform such labor activities in the kitchen. Conclusion: This study shows the high exposure to air pollutants emitted in kitchens, increasing the risk of harm to respiratory health of these workers.